2018
DOI: 10.1039/c7ja90059g
|View full text |Cite
|
Sign up to set email alerts
|

Atomic spectrometry update – a review of advances in environmental analysis

Abstract: This is the 29th annual review of the application of atomic spectrometry to the chemical analysis of environmental samples. This Update refers to papers published approximately between September 2012 and July 2013 and continues the series ofAtomic Spectrometry Updates (ASUs) Developments in geochemical analysis included the production and (re)certification of new geological RMs for bulk, isotopic and microspatial analysis. Optimisation of LA-ICP-MS techniques for the interrogation of geochemical samples con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 493 publications
0
14
0
1
Order By: Relevance
“…The samples were analyzed by X-ray fluorescence [36] using a hand-held XRF Spectrometer DELTA CLASSIC (USA). We used the CONOSTAN calibration standard.…”
Section: Estimating Several Elementsmentioning
confidence: 99%
“…The samples were analyzed by X-ray fluorescence [36] using a hand-held XRF Spectrometer DELTA CLASSIC (USA). We used the CONOSTAN calibration standard.…”
Section: Estimating Several Elementsmentioning
confidence: 99%
“…The authors did point out, however, that in‐field methods would need to be developed to accommodate their findings (Rouillon & Taylor, ). On the other hand, others have suggested that calibration and data processing is still an issue that requires further development (Butler, Cairns, Cook, & Davidson, ).…”
Section: Field‐portable Equipment and Its Role In Environmental Forenmentioning
confidence: 99%
“…Metal leaching is another concern for multirun regeneration, which was studied with AAS (Butler et al 2015). Silver content of Ag X O@SBA-15 in multiple runs was measured as 15.0%, 15.2%, 15.4%, 15.5% and 15.6%, respectively ( Fig.…”
Section: Sorbent Characterizationsmentioning
confidence: 99%